Environmental Risk Factors of Leptospirosis: Systematic Review - Maulana, Muchsin; Stefani, Devi; Matahari, Ratu; Wulandari, Wan Karmida (Epidemiology and Society Health Review (ESHR), 2024)
Background: Leptospirosis is a zoonotic disease caused by the bacteria Leptospira sp. The incidence of Leptospirosis ranges from 0.1 to 10 per 100,000 per year globally. GIS is a tool to visualize data that considers effectiveness and efficiency when determining the priority areas of particular disease control. Method: This systematic review was based on some databases, Google Scholar, PubMed, and the BASE, for articles published from 2010 to 2020. PRISMA guideline was used during data screening. Results: Eight articles were reviewed that showed a pattern of distribution of cases of Leptospirosis: clustered, evenly, and randomly. We also found 15 environmental factors that influence Leptospirosis distribution:  the existence of the river, precipitation, sunshine, a history of the flood, the existence of the gutter, the condition of the garbage disposal, the existence of rice fields, the presence of vegetation, trap success, the existence of the road, the ownership of the pet, the presence of rats, altitudes, and land-use. Conclusion: 15 identified environmental risk factors influence the incidence of Leptospirosis, namely the existence of rivers, history of flooding, the existence of gutters, waste disposal conditions, rainfall, the existence of rice fields, population density, the existence of vegetation, the success of traps, the existence of ponds, the existence of roads, livestock ownership, presence of rats, altitude, and land use.